Hubungan Koordinasi Mata-Tangan Dengan Kemampuan Passing Bawah Pada Tim Bolavoli Putri STKIP Kie Raha Kota Ternate - Alief Lam Akhmady; Firda M. Duwila (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the relationship between eye-hand coordination and the ability to pass down in volleyball at the STKIP Kie Raha women's volleyball team, Ternate City. This research is a research with correlational design. The subject of this research is the women's volleyball team STKIP Kie Raha Ternate City, totaling 20 athletes. Analysis of the data using the Pearson product moment correlation formula at a significant level = 0.05. The findings in this study indicate that there is a very significant relationship between eye-hand coordination and the ability to pass down in volleyball on the STKIP Kie Raha women's volleyball team, Ternate City. The results of the calculation of data analysis of the two variables show that, r-count = 0.959 > r table = 0.456 at a significant level = 0.05. So it can be concluded that there is a very significant relationship between eye-hand coordination and the ability to pass down in volleyball on the STKIP Kie Raha women's volleyball team, Ternate City